Measuring Disparities in Health Status and in Access and Use of Health Care in OECD Countries - de Looper, Michael (OECD Publishing, 2009)
Most OECD countries have endorsed as major policy objectives the reduction of inequalities in health status and the principle of adequate or equal access to health care based on need. These policy objectives require an evidence-based approach to measure progress. This paper assesses the availability and comparability of selected indicators of inequality in health status and in health care access and use across OECD countries, focussing on disparities among socioeconomic groups. These indicators are illustrated using national or cross-national data sources to stratify populations by income, education or occupation level. In each case, people in lower socioeconomic groups tend to have a higher rate of disease, disability and death, use less preventive and specialist health services than expected on the basis of their need, and for certain goods and services may be required to pay a proportionately higher share of their income to do so
Keywords: Social Issues/Migration/Health